PENGARUH KUALITAS LAYANAN DAN PENANGANAN KOMPLAIN TERHADAP KEPUASAN SERTA LOYALITAS PELANGGAN PADA AUTO 2000 CABANG CILEDUG JAKARTA - Martiwi, Rini; Ryad, Ahmad; Karlina, Eulin (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract  –  In industrial products and services, the handling of complaints can be used as a measure of the quality of products and services offered, one of them is in the automotive business (dealer). The purpose of this study is to prove and analyze the effect of quality of service and complaint handling to customer satisfaction, as well as customer loyalty Auto 2000 Ciledug Jakarta. Research method used in this study is explanatory research. The number of respondents in this study were 200 respondents. The means of analyis in this research is the structural equation modeling (SEM). The results showed that all three influenced one another. Customer satisfaction can be increased by improving the quality of service and complaint handling. Keywords: complaints, loyalty, quality of service, satisfaction